Inhibition of neutrophil lysosome-phagosome fusion associated with influenza virus infection in vitro. Role in depressed bactericidal activity. - J S Abramson; J C Lewis; D S Lyles; K A Heller; E L Mills; D A Bass (The Journal of Clinical Investigation, 1982)
The present study examined the effect of various unopsonized strains of influenza A virus on release of myeloperoxidase (MPO) and acid phosphatase in polymorphonuclear leukocytes (PMNL). These results were correlated with the effect that these same viruses had on bactericidal activity in PMNL. Several strains of virus inhibited the fusion of azurophil granules with phagosomes containing Staphylococcus aureus. These same strains inhibited the extracellular release of MPO from PMNL (39-59%) and caused depressed killing (42-77%). In contrast, one of the influenza viruses (X-47a) did not inhibit PMNL MPO release or killing. The data indicate a close relationship between the ability of influenza virus to ablate normal intracellular lysosome-phagosome fusion with subsequent depression of bactericidal functions of PMNL. Images